Mortgage Rights over Property Involving Foreign Nationals: Legal Risks and Reform in Indonesia - Alayna Lita Agzia Khalfani; Mira Novana Ardani (Law Development Journal, 2026)
This study aims to analyze the legal position of mortgage rights (Hak Tanggungan) over land or property owned or controlled by foreign nationals in the Indonesian secured transactions system, as well as to identify the legal risks faced by creditors and the corresponding mitigation measures. This research employs a normative juridical method with statutory, conceptual, and case approaches, analyzed using a prescriptive-analytical framework. The findings indicate that mortgage rights related to foreign nationals are legally valid only when imposed on the Right of Use (Hak Pakai) in accordance with Article 4 paragraph (2) of the Mortgage Law. Conversely, the imposition of mortgage rights over freehold land (Hak Milik) that is de facto controlled by foreign nationals through nominee arrangements is potentially null and void, as it violates the nationality principle in Indonesian agrarian law. Furthermore, creditors face multidimensional legal risks, including invalidity of security, unenforceability of execution, regulatory risks, and potential criminal liability. The study also reveals that effective risk mitigation requires a comprehensive approach, including rigorous legal due diligence, and appropriate structuring of collateral. Therefore, regulatory harmonization and strengthened supervisory mechanisms are necessary to enhance legal certainty and protection in mortgage practices involving foreign nationals.